2011
DOI: 10.1167/iovs.10-5209
|View full text |Cite
|
Sign up to set email alerts
|

Connective Tissue Growth Factor Is Increased in Pseudoexfoliation Glaucoma

Abstract: Increased levels of CTGF in the aqueous humor of PXF patients likely has pathologic significance through increased production of fibrillin-1 by TM cells through activation of p42/44 MAPK, p38 MAPK, and JNK pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(56 citation statements)
references
References 42 publications
5
48
0
3
Order By: Relevance
“…The AH is composed of ions (Na + , K + , Ca 2+ , Mg 2+ , Cl -, HCO 3 -), crystalloid or low molecular weight substances (glucose, ascorbate, lactate, pyruvate, urea, H2O2, amino acids, etc. ), colloidal or high molecular weight substances, such as proteins (Borazan et al, 2010;Browne et al, 2011;Ghanem et al, 2011;Lim et al, 2010), lipids (Jahn et al, 1983), biologically active substances (catecholamines, eicosanoids, hormones, etc.) as well as some miscellaneous substances such as hyaluronic acid, hyaluronidase, etc.).…”
Section: Composition Of the Aqueous Humormentioning
confidence: 99%
See 1 more Smart Citation
“…The AH is composed of ions (Na + , K + , Ca 2+ , Mg 2+ , Cl -, HCO 3 -), crystalloid or low molecular weight substances (glucose, ascorbate, lactate, pyruvate, urea, H2O2, amino acids, etc. ), colloidal or high molecular weight substances, such as proteins (Borazan et al, 2010;Browne et al, 2011;Ghanem et al, 2011;Lim et al, 2010), lipids (Jahn et al, 1983), biologically active substances (catecholamines, eicosanoids, hormones, etc.) as well as some miscellaneous substances such as hyaluronic acid, hyaluronidase, etc.).…”
Section: Composition Of the Aqueous Humormentioning
confidence: 99%
“…Several studies have shown that AH can promote proliferation of cells in tissue culture (Albrink and Wallace, 1951;Benezra and Sachs, 1974;Herschler et al, 1980;Herschler and Tucson, 1983) or inhibit cellular growth (Kornblueth and Tenenbaum, 1956). While these opposing findings may perhaps be explained by the different experimental conditions and procedures, the possibility of AH being a growth modulator is a real possibility since a number of growth factors are present in the AH (Borazan et al, 2010;Browne et al, 2011;Ghanem et al, 2011;Lim et al, 2010). AH may be thought of as a growth medium in which stimulatory agents and cytotoxic factors act to affect changes in cell number, morphology and function.…”
Section: Composition Of the Aqueous Humormentioning
confidence: 99%
“…104 Given its profibrotic tendencies, it became a protein of interest in surgical models, demonstrating increased expression following glaucoma filtration surgery in rabbits and being associated with an elevated risk of bleb failure. 105,106 The putative role of CTGF in human glaucoma pathophysiology was first identified in pseudoexfoliation syndrome, 107,108 and attention soon focused on how CTGF regulates TM matrix deposition, 109,110 cellular tone, 111 and aqueous outflow facility. 112,113 In one promising recent study, the prostaglandin analog fluprostenol was found to mitigate CTGF-induced fibrogenesis in cultured human TM cells.…”
mentioning
confidence: 99%
“…Furthermore, PEX glaucoma is frequently resistant to medical management, and postoperative inflammation is common (Allingham et al 2005). Browne et al (2011) found that PEX glaucoma contained higher level of aqueous humour connective tissue growth factor (CTGF) than primary open angle glaucoma and PEX without glaucoma. We investigated the role of the CTGF gene in PEX and further analysed the association with PEX glaucoma.…”
Section: Referencesmentioning
confidence: 99%